Studies on decomposition behavior of oxalic acid waste by UVC photo-Fenton advanced oxidation process - Kim, Jin-Hee; Lee, Hyun-Kyu; Park, Yoon-Ji; Lee, Sae-Binna; Choi, Sang-June; Oh, Wonzin; Kim, Hak-Soo; Kim, Cho-Rong; Kim, Ki-Chul; Seo, Bum-Chul (Nuclear engineering and technology, 2019)
A UVC photo-Fenton advanced oxidation process (AOP) was studied to develop a process for the decomposition of oxalic acid waste generated in the chemical decontamination of nuclear power plants. The oxalate decomposition behavior was investigated by using a UVC photo-Fenton reactor system with a recirculation tank. The effects of the three operational variables―UVC irradiation, H2O2 and Fenton reagent―on the oxalate decomposition behavior were experimentally studied, and the behavior of the decomposition product, CO2, was observed. UVC irradiation of oxalate resulted in vigorous CO2 bubbling, and the irradiation dose was thought to be a rate-determining variable. Based on the above results, the oxalate decomposition kinetics were investigated from the viewpoint of radical formation, propagation, and termination reactions. The proposed UVC irradiation density model, expressed by the first-order reaction of oxalate with the same amount of H2O2 consumption, satisfactorily predicted the oxalate decomposition behavior, irrespective of the circulate rate in the reactor system within the experimental range.